• Jan 27th 2009, 10:06 AM
Leona_Marie
4x + 12 = 3(4 - X)
well 4x + 12 = 12 - 3x
4x + 12 -12 =12 - 3x -12
= 4x -12 = 12 -12 -9
= -8x -9
=8x/8 -9/8 = - 1 1/8 book says answer is 0 . not thinking right can someone help.
• Jan 27th 2009, 10:10 AM
Chris L T521
Quote:

Originally Posted by Leona_Marie
4x + 12 = 3(4 - X)
well 4x + 12 = 12 - 3x
4x + 12 -12 =12 - 3x -12
= 4x -12 = 12 -12 -9
= -8x -9
=8x/8 -9/8 = - 1 1/8 book says answer is 0 . not thinking right can someone help.

The line in red is where you started to go wrong...

You have \$\displaystyle 4x+12-12=12-3x-12\implies 4x+(12-12)=-3x+(12-12)\$

Note that I put some terms in parenthesis to make the next step in the process easier to see. Can you continue?
• Jan 27th 2009, 10:39 AM
Leona_Marie
Quote:

Originally Posted by Chris L T521
The line in red is where you started to go wrong...

You have \$\displaystyle 4x+12-12=12-3x-12\implies 4x+(12-12)=-3x+(12-12)\$

Note that I put some terms in parenthesis to make the next step in the process easier to see. Can you continue?

switching 12 around doesnt make the answer 0
4x +12 -12 = -3x + 12 -12
= 4x = -3x
=4x +3x = -3x + 3x
=7x not 0 plus the only rule is that whatever you do to the left you have to do to the right. the right in this equation is -3x so -3x -12, which is 3x -12 ,would be -9
• Jan 27th 2009, 12:33 PM
masters
Quote:

Originally Posted by Chris L T521
The line in red is where you started to go wrong...

You have \$\displaystyle 4x+12-12=12-3x-12\implies 4x+(12-12)=-3x+(12-12)\$

Note that I put some terms in parenthesis to make the next step in the process easier to see. Can you continue?

Quote:

Originally Posted by Leona_Marie
switching 12 around doesnt make the answer 0
4x +12 -12 = -3x + 12 -12
= 4x = -3x
=4x +3x = -3x + 3x
=7x not 0 plus the only rule is that whatever you do to the left you have to do to the right. the right in this equation is -3x so -3x -12, which is 3x -12 ,would be -9

Go back and look at what Chris has shown you.

\$\displaystyle 4x+12-12=12-3x-12\implies 4x+(12-12)=-3x+(12-12)\$

\$\displaystyle 4x+0=-3x+0\$

\$\displaystyle 4x=-3x\$

\$\displaystyle 4x+3x=0\$

\$\displaystyle 7x=0\$

\$\displaystyle x=0\$
• Jan 27th 2009, 03:13 PM
Leona_Marie
masters , please explain to me how 7x = 0 or x = 0 the only thing I would know how to do is to devide 7x/7 0/7 = 0 ? plus Ive never seen wher you can swap + -3x + 12 or visa versa is this the case or am I missing something again. in other words the question was written out12 -3x so shouldnt the number come off the right. I think I just got it please verify.
• Jan 27th 2009, 05:28 PM
TheMasterMind
Quote:

Originally Posted by Leona_Marie
4x + 12 = 3(4 - X)
well 4x + 12 = 12 - 3x
4x + 12 -12 =12 - 3x -12
= 4x -12 = 12 -12 -9
= -8x -9
=8x/8 -9/8 = - 1 1/8 book says answer is 0 . not thinking right can someone help.

4x+12=12-3x

4x+3x=12-12

7x=0

x=0

expand,collect, and you're done!
• Jan 27th 2009, 05:32 PM
TheMasterMind
Quote:

Originally Posted by Leona_Marie
masters , please explain to me how 7x = 0 or x = 0 the only thing I would know how to do is to devide 7x/7 0/7 = 0 ? plus Ive never seen wher you can swap + -3x + 12 or visa versa is this the case or am I missing something again. in other words the question was written out12 -3x so shouldnt the number come off the right. I think I just got it please verify.

yes 0/7 is what masters did.. which = 0 and you can always swap to other sides of the equation to collect like terms(as long as you change the sign)